2015
DOI: 10.1002/2015gb005188
|View full text |Cite
|
Sign up to set email alerts
|

Explicitly representing soil microbial processes in Earth system models

Abstract: Microbes influence soil organic matter decomposition and the long‐term stabilization of carbon (C) in soils. We contend that by revising the representation of microbial processes and their interactions with the physicochemical soil environment, Earth system models (ESMs) will make more realistic global C cycle projections. Explicit representation of microbial processes presents considerable challenges due to the scale at which these processes occur. Thus, applying microbial theory in ESMs requires a framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
324
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 340 publications
(329 citation statements)
references
References 186 publications
(325 reference statements)
4
324
1
Order By: Relevance
“…The values of those parameters may be quite different under field conditions. Evaluation of their applicability under a wide range of field conditions will require an integrated approach, such as applications of model-data fusion using a range of field experiments (Wieder et al, 2016). This will eventually lead to a better understanding of the significance of microbial activity on soil carbon decomposition and more accurate predictions of carbon-climate interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of those parameters may be quite different under field conditions. Evaluation of their applicability under a wide range of field conditions will require an integrated approach, such as applications of model-data fusion using a range of field experiments (Wieder et al, 2016). This will eventually lead to a better understanding of the significance of microbial activity on soil carbon decomposition and more accurate predictions of carbon-climate interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, conventional linear soil carbon models predict that soil carbon will decrease with increased temperature, all else being equal (Jenkinson et al, 1991), whereas the nonlinear models predict that the soil carbon can decrease or increase, depending on the temperature sensitivity of microbial growth efficiency and turnover rates (Frey et al, 2013;Hagerty et al, 2014;Li et al, 2014). However, the nonlinear models have yet to be validated against field measurements as extensively as the conventional linear soil carbon models (Wieder et al, 2016). They also have some undesirable features, particularly the presence of strong oscillations or bifurcations (Manzoni and Porporato, 2007;Wang et al, 2014) in their dynamics that are not observed in real-world systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, use of a more mechanistic module of Rh in ecosystem models and ESMs is warranted to address important environmental controls that modulate the apparent temperature sensitivity of Rh across different systems and among seasons within a system (Davidson and Janssens, 2006;von Lützow and Kögel-Knabner, 2009;Wieder et al, 2015;Luo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, growth respiration is only due when substrate for growth is available. Because of the explicit and mechanistic link between microbial activity and soil organic matter degradation, inclusion of microbial models in Earth system models may have the potential to ultimately reduce uncertainty in climate-carbon feedback in the face of climate change because of the explicit link between microbial activity and soil organic matter degradation (Todd-Brown et al, 2012Wieder et al, 2015a).…”
Section: Sihi Et Al: Comparing Models Of Microbial-substrate Intementioning
confidence: 99%